Developing Educational Game of Mathematics Calculating Concept for Elementary School - Ahmad Chamsudin; Ajeng Budi Sucining Asih (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2021)
This learning media aims to assist students in increasing understanding of mathematical concepts, being able to explain the relationship between concepts and the application of concepts or algorithms in a flexible, accurate, efficient and precise way in problem solving. The advantage of this educational game is that there are several materials that are equipped with animations, sound images and quizzes so that they can generate enthusiasm and interest in students in learning mathematics. The results of observations that have been made at SDN 1 Trangsan are that mathematics learning carried out in schools is not fun or still uses the lecture method in learning so that mathematical concepts are not conveyed. In this study, the method used was RD (Research and Development) and the ADDIE development method (analysis, development, design, implementation, evaluation). This media has been tested on 3 media experts and obtained the result that the average coefficient V is 0.90 and can be declared valid. While the results of the reliability test from media experts is 0.710 and can be stated as strong reliability. While the material was tested on 2 accompanying teachers in elementary schools who obtained an average value of coefficient V of 0.92 which was declared valid. The results of the material expert reliability test obtained a value of 0.768 and declared strong reliability. The results of the interpretation test of the percentage of tests carried out by 10 respondents or students obtained a percentage value of 67.4% which was included in the